Studies on the properties of low density polyethylene composites filled seafood waste shell powder [Studiul proprietăţilor compozitelor pe bază de polietilenă de joasă densitate armate cu pulbere din cochiliile moluştelor marine] - (:unkn) unknown (Procema SA, 2016)
In this study low density Polyethylene (LDPE)-based composites are prepared using mussel-oyster shell powder as natural filler. Filler contents in the LDPE were 5, 10 and 15 wt%. The mechanical properties of the polymer composites were investigated. Some mechanical properties of low density polyethylene bio composites have effected much by the addition of mussel-oyster shell powder. For example, the results showed that the elasticity modulus, Izod impact strength, hardness and density of composites improved with increasing the mussel and oyster contents. The addition of fillers to the LDPE changed the wear rate of the composites. LDPE filled with a high level content of mussel and oyster showed higher wear rate than pure LDPE under dry sliding. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM). This study has shown that the composites treated with mussel-oyster shell powder as natural additive and as an inorganic particle-filled polymer will be attractive due to their improved mechanical properties of LDPE. © 2016, Procema SA. All rights reserved.
Keywords: Low density polyethylene; Mechanical properties; Mussel; Oyster; Wear